2018
DOI: 10.3389/fmolb.2018.00019
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin-Bound Cullin-Ring Ligases: Regulatory Roles in DNA Replication and Potential Targeting for Cancer Therapy

Abstract: Cullin-RING (Really Interesting New Gene) E3 ubiquitin ligases (CRLs), the largest family of E3 ubiquitin ligases, are functional multi-subunit complexes including substrate receptors, adaptors, cullin scaffolds, and RING-box proteins. CRLs are responsible for ubiquitination of ~20% of cellular proteins and are involved in diverse biological processes including cell cycle progression, genome stability, and oncogenesis. Not surprisingly, cullins are deregulated in many diseases and instances of cancer. Recent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 222 publications
0
43
0
Order By: Relevance
“…The above observations suggest that BUB3 is a substrate of CRL4 and that its interaction with CRL4 facilitates its ubiquitination and degradation during mitosis. Since we observed that BUB3 levels were stable, and even increased, during interphase, we sought to identify a mechanism that would prevent BUB3 degradation during interphase despite the presence of active, chromatinbound CRL4 5,14 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above observations suggest that BUB3 is a substrate of CRL4 and that its interaction with CRL4 facilitates its ubiquitination and degradation during mitosis. Since we observed that BUB3 levels were stable, and even increased, during interphase, we sought to identify a mechanism that would prevent BUB3 degradation during interphase despite the presence of active, chromatinbound CRL4 5,14 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Transitions between these major events are orchestrated by posttranslational modifications to ensure the preservation of genomic information [1][2][3][4] . Ubiquitin ligases regulate cell cycle progression by mediating the timely degradation of effector proteins [5][6][7][8] . Cullin-RING ubiquitin ligase complex 4 (CRL4) associates with a diverse array of substrates through a series of WD motif containing substrate receptors known as DDB1-CUL4-associated factors (DCAFs) 9 .…”
mentioning
confidence: 99%
“…Both high LOXL2 levels and its perinuclear localization are associated with poor outcome and lower survival rates of patients with breast cancer (Ahn et al, 2013;Moreno-Bueno et al, 2011). Furthermore, both RUVBL2 and CRL4B complex are also known to play important roles in cancer biology (Grigoletto et al, 2011;Grigoletto et al, 2013;Jang et al, 2018;Mao and Houry, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…CRLs are a very large family of multisubunit E3 ubiquitin ligases containing 1 of 8 cullin scaffolds (Bulatov and Ciulli, 2015;Jang et al, 2018). CRL4s are composed of cullin4(A/B), DDB1 adaptor, RBX1 E2-binding RING finger, and one of many substrate-recruiting receptors (Hannah and Zhou, 2015).…”
Section: Cullin-ring Ligase (Crl) 4 Cdt2mentioning
confidence: 99%